ARCHAEOLOGICAL RESEARCH IN THE SOUTH CAUCASUS IN THE GEOPOLITICAL CONTEXT IN THE XIX CENTURY - Abdulla Abdullayev, (International Journal of Innovative Technologies in Social Science, 2025)
The scientific interpretation of archaeological samples of material culture is not always organized objectively. Especially in the early period, archaeological excavations have sometimes been interpreted for various political-historical purposes. In our changing and developing world for the sake of objectivity, it is necessary to consider and analyze doubtful points. The formation of the ancient and medieval history of peoples and geography was part of the aggressive policy of the empire of the new era. The implemented studies were interpreted not from the point of view of objectivity, but against the background of geopolitical interests. These elements can be observed also in the historical-archaeological research organized by the Tsarist Russian Empire in the South Caucasus in the XlX century. The leading direction in the implementation of these studies was that culture and its principles of succession were associated with the resources of imperial forces. Although the Tsarist Empire collapsed after World War I, the research conducted in the region was influenced by the political interests of the other Russian Empire (the Soviet Union).